Cell-Mediated Immune Ontogeny Is Affected by Sex but Not Environmental Context in a Long-Lived Primate Species - Behringer, Verena; Deimel, Caroline; Stevens, Jeroen M. G.; Kreyer, Melodie; Lee, Sean M.; Hohmann, Gottfried; Fruth, Barbara; Heistermann, Michael (Frontiers in Ecology and Evolution, 2021)
Ecoimmunology conceptualizes the role of immunity in shaping life history in a natural context. Within ecoimmunology, macroimmunology is a framework that explains the effects of habitat and spatial differences on variation in immune phenotypes across populations. Within these frameworks, immune ontogeny – the development of the immune system across an individual life span – has received little attention. Here, we investigated how immune ontogeny from birth until adulthood is affected by age, sex, and developmental environment in a long-lived primate species, the bonobo. We found a progressive, significant decline of urinary neopterin levels, a marker for the cell-mediated immune response, from birth until five years of age in both sexes. The overall pattern of age-related neopterin changes was sex-specific, with males having higher urinary neopterin levels than females in the first three years of life, and females having higher levels than males between six to eight years. Environmental condition (zoo-housed vs. wild) did not influence neopterin levels, nor did age-related changes in neopterin levels differ between environments. Our data suggest that, the post-natal development of cell-mediated immune ontogeny is sex-specific but does not show plasticity in response to environmental conditions in this long-lived primate species. This indicates that cell-mediated immune ontogeny in the bonobo follows a stereotypic and maybe a genetically determined pattern that is not affected by environmental differences in pathogen exposure and energy availability, but that sex is an important, yet often overlooked factor shaping patterns of immune ontogeny. Investigating the causes and consequences of variation in immunity throughout life is critical for our understanding of life-history evolution and strategies, mechanisms of sexual selection, and population dynamics with respect to pathogen susceptibility. A general description of sex-specific immune ontogeny as done here is a crucial step in this direction, particularly when it is considered in the context of a species’ ecology and evolutionary history.